2007
DOI: 10.1111/j.1600-0528.2007.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Number of teeth – a predictor of mortality in 70‐year‐old subjects

Abstract: The result showed that each remaining tooth at age 70 decreased the 7-year mortality risk by 4%. The difference between edentulous subjects and dentate subjects with >or=20 teeth regarding 7-year mortality was significantly higher in the last compared to the first cohort. The number of teeth was a significant predictor of mortality independent of health factors, socio-economic status and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 39 publications
4
89
0
6
Order By: Relevance
“…Holm-Pedersen et al followed a cohort of 573 70-year-old Danish non-disabled elders over an observation period of 21 years and reported that 'being edentulous or having 1-9 teeth was associated with onset of disability at age 75 and 80 years' and that 'persons being edentulous at age 70 were significantly higher at risk of mortality 21 years later (Hazard ratio 1.26, 95% CI 1.03-1.55)' 68 . Other authors confirmed these findings with a shorter observation period and reported that this correlation was even more evident in men than in women 69 . They concluded that 'The number of teeth was a significant predictor of mortality independent of health factors, socio-economic status and lifestyle'.…”
Section: Longevitymentioning
confidence: 61%
“…Holm-Pedersen et al followed a cohort of 573 70-year-old Danish non-disabled elders over an observation period of 21 years and reported that 'being edentulous or having 1-9 teeth was associated with onset of disability at age 75 and 80 years' and that 'persons being edentulous at age 70 were significantly higher at risk of mortality 21 years later (Hazard ratio 1.26, 95% CI 1.03-1.55)' 68 . Other authors confirmed these findings with a shorter observation period and reported that this correlation was even more evident in men than in women 69 . They concluded that 'The number of teeth was a significant predictor of mortality independent of health factors, socio-economic status and lifestyle'.…”
Section: Longevitymentioning
confidence: 61%
“…38 The important relationship between the number of remaining teeth and mortality, irrespective of medical, social and economic factors, was determined by observing 4 cohorts of over 1,800 Swedes aged over 70 years. 39 The findings regarding tooth loss as an independent weak risk factor for stroke was made on the basis of a survey of more than 13,000 Americans aged over 60 years. 40 In young seniors in Wrocław, no meaningful relationship was found between body mass expressed by BMI index and number of teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss is related to subclinical atherosclerosis in men but not in women (Desvarieux et al, 2004). The number of teeth also seems to be a predictor of mortality independent of health factors and socioeconomic status but with clear-cut sex differences (Osterberg et al, 2008). IRR, incidence rate ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%